Leadership Programs And Models AT SMP Negeri 31 Medan - Wasiyem Wasiyem; Syahrida Suryani Hasibuan; Tengku Muhammad Faris Nurfikri (International Journal Of Health Science, 2024)
Education is a process of learning, skills and routines of a group of people that are inherited from one offspring to the next which is usually obtained through the teaching process. Leadership is the influence generated between individuals, which is carried out under certain circumstances and directed through the process of communication to achieve certain goals. In the world of education, the role of these leaders is needed in school stakeholders (teachers / staff, employees, students, and school residents). In the context of the leadership program at SMPN 31 Medan, there are challenges when developing leadership initiatives. For example, out of 10 programs submitted to the agency, sometimes these programs do not match or even exceed the plans that have been made, caused by the sudden need to create new programs such as teacher training for the independent curriculum, and so on. The purpose of this study explores the program and leadership model in SMP Negeri 31 Medan. Research methods involve observation, interviews, and analysis, documentation to understand the implementation of educational programs and leadership strategies in such schools. The respondents of this study consisted of the vice principal, a teacher and two students. The results of this study show that the leadership program and model at SMPN 31 Medan has been carried out, this is shown by changes when representatives and principals after carrying out their leadership through planning and reserve programs face every challenge that comes. Next, Leadership of teacher performance has demonstrated effective leadership of teacher performance. This is shown by constructive feedback in accordance with the direction of leadership, namely the principal often directs teachers in a good way also often gives constructive suggestions and this is responded well by teachers. And, Leadership towards students at SMPN 31 Medan has characteristics and provides positive change. It is shown that students obey and obey the rules of the school and the sense of fairness felt by students because no individuals are found to be treated specifically or deliberately ignored.